Womb to Growth: How Maternal Anemia and Low Birth Weight Shape Toddler Stunting - Maternity, Dainty; Puspitasari, Dian (Poltekkes Kemenkes Tanjung Karang, Indonesia, 2024)
attention from all sectors. One of the main factors influencing stunting is anemia during pregnancy. Object: Therefore, this study aimed to determine the relationship between a history of maternal anemia during pregnancy and stunting in toddlers in the Banjarsari Community Health Center, North Metro, in 2025. Method: This research used a quantitative case-control design. The population consisted of 622 mothers with toddlers aged 24–59 months in the Banjarsari area. The sample size, calculated using an unpaired categorical comparative formula, totaled 60 respondents (20 cases and 40 controls) with a 1:2 ratio. Sampling was done using stratified random sampling. Data collection involved observation, interviews, and documentation through checklists, stadiometers, and KIA books. Results: Data were analyzed using univariate and bivariate (chi-square) tests. The results showed that 33.3% of mothers experienced anemia during pregnancy. Statistical analysis indicated a significant relationship between maternal anemia during pregnancy and stunting in toddlers (p = 0.012, OR = 4.210, 95% CI = 1.331–13.320). Conclusion: The study concluded that maternal anemia is significantly associated with stunting. Health workers are advised to strengthen maternal and child health promotion and empower community cadres to provide nutritional education for pregnant women and toddlers.